2016
DOI: 10.1002/jms.3816
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐isotopic signatures of organic and conventional Italian pasta along the production chain

Abstract: The variability of stable isotope ratios (δ(2) H, δ(13) C, δ(15) N, δ(18) O and δ(34) S) along the production chain of pasta (durum wheat, flour and pasta) produced by using both conventional and organic farming systems in four Italian regions in 2 years was investigated. The aim was to evaluate if and how the farming system and geographical origin affect stable isotope ratios determined along the production chain. Irrespective of the processing technology, 65% of the samples were correctly classified accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
5
16
0
Order By: Relevance
“…Very few studies reported the δ 2 H values for wheat. Our results are in agreement with the previously reported results for Italian wheat and its products …”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Very few studies reported the δ 2 H values for wheat. Our results are in agreement with the previously reported results for Italian wheat and its products …”
Section: Resultssupporting
confidence: 94%
“…There was no significant variation in δ 13 C between Zhaoxian and Huixian probably because both regions experience the same climatic conditions and located at very close altitude (39 and 82 m) (Table ). In a previous study, a similar trend for δ 13 C was reported by Bontempo and colleagues . In this study, significant variation in δ 13 C among different regions Yangling and Zhaoxian/Huixian is mainly because of altitude difference as it had been documented that δ 13 C values increased with a rise in altitude .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The highest δ 34 S values in Iblei forages were also observed in Iblei cheese while lower δ 34 S values were detected in Catania green forage and cheese. In this area the low values could be related to the volcanic sulfur present in this region, as observed in the case of Tuscany pasta by Bontempo et al . Our results suggest that the different geo‐morphologic, pedologic and climatic conditions of the three areas of production might have affected the δ 34 S values in the soil, in the locally produced feeds supplied to the ewes and, finally, in the cheese.…”
Section: Discussionsupporting
confidence: 72%